2019
DOI: 10.3390/ma12233939
|View full text |Cite
|
Sign up to set email alerts
|

Curing Kinetic Parameters of Epoxy Composite Reinforced with Mallow Fibers

Abstract: Knowledge about the curing behavior of a thermosetting resin and its composites includes the determination of kinetic parameters and constitutes an important scientific and technological tool for industrial process optimization. In the present work, the differential scanning calorimetry (DSC) technique was used to determine several curing parameters for pure epoxy and its composite reinforced with 20 vol % mallow fibers. Analyses were performed with heating rates of 5, 7.5, and 10 °C/min, as per the ASTM E698 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Within the investigated temperature range, the curves did not present any relevant event for this analysis, which suggests that the glass transition temperature of the composite shifted because of the presence of the reinforcement. Exothermic peaks at around 114 °C are related to a possible curing of the polymer matrix [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the investigated temperature range, the curves did not present any relevant event for this analysis, which suggests that the glass transition temperature of the composite shifted because of the presence of the reinforcement. Exothermic peaks at around 114 °C are related to a possible curing of the polymer matrix [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of composites, the proportions used were 10, 20 and 30% by volume of fiber, which correspond in absolute terms of mold loading to 14.12, 28.25 and 42.37 g, respectively. The density value of the epoxy resin was based on data reported elsewhere for the same epoxy [ 28 ]. For the DGEBA/TETA, an estimate of 1.11 g/cm 3 was considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another particular situation, for epoxy/barium ferrite/polyaniline composites, Saad et al [41] considered that the protonated amine-imine groups of polyaniline act as epoxy-opening initiators to accelerate the cure reaction. Finally, in a quite different epoxy composite system, in which mallow fibres give rise to a very slight acceleration of the cure, Nascimento et al [43] concluded that mallow fibres act as "nucleation sites".…”
Section: Epoxy Compositesmentioning
confidence: 99%
“…The most common observation is that the cure reaction of epoxy composites is accelerated by the addition of fillers (e.g., [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]), most of these systems being based on DGEBA epoxy resin, and cured with methylene dianiline [ 33 , 34 ], anhydride [ 36 , 42 ], or amines [ 35 , 39 , 43 ]. A wide variety of fillers is included here: zeolite [ 33 , 34 , 36 ], zirconium tungstate [ 37 ], alumina [ 39 , 42 ], barium ferrite/aniline [ 41 ], carbon black and carbon fibres [ 35 ], aluminium nitride [ 40 ], silica [ 38 ] and mallow fibres [ 43 ]. The advance of the curing process is typically identified by a reduction in the peak exotherm temperature in a non-isothermal cure or by a decrease in the time to the peak exotherm in an isothermal cure.…”
Section: Cure Kineticsmentioning
confidence: 99%